The Genome of the CTG(Ser1) Yeast Scheffersomyces stipitis Is Plastic - Samuel Vega-Estévez; Andrew Armitage; Helen J. Bates; Richard J. Harrison; Alessia Buscaino (mBio, 2021)
Genomes contain genes encoding the information needed to build the organism and allow it to grow and develop. Genomes are described as stable structures where genes have specific positions within a chromosome.